Clinicopathological aspects and prevalence of human papillomavirus in anal cancer - Aguiar, Marina Tayla Mesquita; Bosso, Natália Carelli de Castro; Leal, Caio Bruno Quinta de Souza; de Lira, Clerlhan Ferreira; Cabral, Lázara Alyne Oliveira; Silva, Antonio Márcio Teodoro Cordeiro; Saddi, Vera Aparecida (Journal of Coloproctology, 2014)
Anal cancer is relatively rare; however, its incidence has increased in recent years. Several risk factors are associated with the development of anal cancer, including age older than 50 years, low-fiber diet, chronic anal fistulas, smoking, multiple partners, anal intercourse practice, Human Immunodeficiency Virus infection and immunosuppression. However, the presence of human papillomavirus represents the main risk factor for the development of anal cancer. The aim of this study was to evaluate the clinicopathological aspects of a series of patients with anal carcinomas diagnosed in Hospital Araújo Jorge, Goiânia-Goiás, as well as the prevalence of human papillomavirus genome in these tumors. Clinical, pathological and socio-demographic data were collected from the respective medical files and paraffin blocks containing anal carcinomas specimens were used for DNA extraction and detection of human papillomavirus, by means of polymerase chain reaction, using short PCR fragment primers. Forty-three cases were selected and had the data analyzed, while 38 cases were tested for human papillomavirus genome detection. Among the evaluated patients, 62.8% were women; 53.4% of tumors were squamous cell carcinoma and 46.5% of the patients were aged between 60 and 75 years. Risk factors, such as smoking (39.5%) and alcoholism (20.9%) were recorded in the studied group. Lymph node metastases were detected in 30.2% of cases and 7.0% had distant metastasis. The detection of human papillomavirus DNA was positive in 76% of cases assessed and this was significantly associated with squamous cell carcinomas. Aggressive behavior and advanced stage of anal cancer described in this study highlight the need for preventive measures that contemplate these tumors, including vaccination against human papillomavirus.
Keywords: Anal cancer; Characteristics; Human papillomavirus; HPV; HPV16; HPV18